2012
DOI: 10.5402/2012/282515
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Mechanical Properties of Polypropylene-Aluminum-Dross Composite

Abstract: Aluminum (Al) dross is a hazardous waste from the secondary smelting of aluminium industries, and safe disposal of this waste is a big challenge to these industries. Dumping of this waste is an environmental hazard to plants, animals, and even human beings. This study is aimed at improving the mechanical properties of polypropylene (PP) by adding Al dross in 2-50 wt% for particle sizes 53 μm and 150 μm. PP-Al-dross composite samples were cast, and ultimate tensile strength (UTS), impact resistance (IR), water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Aluminum wastes, mainly, are disposed of in landfill sites, which may result in leaking of toxic metal ions into the ground water. Also, when aluminum waste comes in contact with water it emits poisonous gases as NH 3 , CH 4 , PH 3 , H 2 , and H 2 S [10,11]. The environmental effects of aluminum scrap from recycled aluminum should be minimized.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Aluminum wastes, mainly, are disposed of in landfill sites, which may result in leaking of toxic metal ions into the ground water. Also, when aluminum waste comes in contact with water it emits poisonous gases as NH 3 , CH 4 , PH 3 , H 2 , and H 2 S [10,11]. The environmental effects of aluminum scrap from recycled aluminum should be minimized.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Direct applications as raw materials in the refractory brick [16] or in the production of inert filling for construction, road paving, mortar components, polymer composites, adsorbents, and mineral wood have been reported [17]. While other researchers have aimed to use them to manufacture other raw materials such as hydrogen gas [18], X-zeolites [19], aluminum sulfate (Al2(SO4)3.18H2O) [20] and alumina with different properties for many applications like catalysis [21,22], cement [23], biomaterials [24] and refractory [16].…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ] In one of these studies, Adeosun et al prepared PP/Al‐dross composites by adding Al‐dross into the PP phase by 2–50% wt. [ 20 ] The authors reported that the ultimate tensile strength of PP improved by 68% (at 15% wt. Al‐dross addition), and the impact resistance did not change considerably for the 15% wt.…”
Section: Introductionmentioning
confidence: 99%